A Novel 3D Paper-Based Immobilized Cultivation Platform for Accelerated Microalgae Growth - Jinxin Guo, Chaocan Li, Yufei Wang, Yuanyuan Song, Daohong Zhang (Forest Chemicals Review, 2022)
Compared to suspended cultivation, immobilized cultivation methods of microalgae were reported to enhance biomass productivity and reduce harvesting cost. In this paper, a 3D microalgae immobilized cultivation method was developed on a paper platform, composed by six 5 mm-diameter wells fabricated with a wax printer. The microalgae immobilized in agar gel were loaded on the top of the wells, which was exposed to air. Agar with higher density was loaded on back of the well (immersed in medium) to both prevent leakage of microalgae and transport nutrients to cells. Results showed that the microalgae entrapped in gels stand on the top of medium grew faster than the microalgae gels immersed in medium, owing to high carbon dioxide concentration and faster transmission rate of air. Meanwhile, six wells under same culturing condition equaled to six cultures in Erlenmeyer flasks, which saved space and medium for cultivation. Furthermore, the microalgae could be obtained easily by just collecting the paper platform. No microalgae growth out of the gel also indicated the recyclable of the culture medium. Microalgae were cultivated on this platform with medium containing different salts as a test. Therefore, this platform represents an alternative for microalgae flask culture and a promising microalgae immobilized cultivation method, with decreased culture cost, time and space, which can be utilized for easier and faster study on microalgae wastewater treatment and biofuel production.